(untitled) (International Journal of Engineering and Computer Science, 2017)
In telecommunications, 4G is the fourth generation of mobile communication technology standards. It is a successor of the third generation (3G) standards. A 4G system provides mobile ultra-broadband Internet access, for example to laptops with USB wireless modems, to smartphones, and to other mobile devices. Conceivable applications include amended mobile web access, IP telephony, gaming services, highdefinition mobile TV, video conferencing, 3D television and Cloud Computing. In order to achieve that a recently proposed concept for 4G standards i.e LTE-Advanced is Cooperative Communication. Cooperative communication allows single antenna mobile (i.e. Single User) to temporary (Logically) share the antenna of other users in a system and thus creates a virtual multiple antenna array that allows it to achieve diversity gain & other benefits of multiple input multiple output (MIMO) systems in a cost effective manner. The scope of this research paper is to evaluate the Performance of Decode and Forward cooperative communication protocol in terms of its bit error rate(BER) throughput and outage probability.